Driving around bends with or without shoulders: The influence of bend direction. (November 2022) - Mecheri, Sami; Mars, Franck; Lobjois, Régis
Highlights: Drivers shifted toward the inner edge on right but not on left bends with shoulders. This occurred at entry, apex, and innermost position with no oncoming traffic. This occurred at apex and innermost position with oncoming traffic. Findings show a previously unreported impact of shoulders on steering behavior. It is argued that drivers view shoulders as a new field of safe travel. Abstract: Paved shoulders have long been used to create "forgiving" roads where drivers can maintain control of their vehicles even when as they drift out of the lane. While the safety benefits of shoulders have been well documented, their effects on driver behavior around curves have scarcely been examined. The purpose of this paper is to fill this gap by assessing whether the addition of shoulders affects driver behavior differently as a function of bend direction. Driver behavior in a driving simulator was analyzed on left and right curves of two-lane rural roads in the presence and absence of 0.75-m and 1.25-m shoulders. The results demonstrated significant changes in drivers' lateral control when shoulders were provided. In the absence of oncoming traffic, the shoulders caused participants to deviate more toward the inner lane edge at curve entry, at the apex and at the innermost position on right bends but not left ones. In the presence of oncoming traffic, this also occurred at the apex and the innermost position, leading participants to spend more time off the lane on right curves. Participants did not slow down in either traffic condition to compensate for steering farther inside, thereby increasing the risk of lane departure on right curves equipped with shoulders. These findings highlight the direction-specific influence of shoulders on a driver's steering control when driving around bends. They provide arguments supporting the idea that drivers view paved shoulders as a new field of safe travel on right curves. Recommendations are made to encourage drivers to keep their vehicle within the lane on right bends and to prevent potential interference with cyclists when a shoulder is present.